(3eNJUQ Yde GdgjFIs - (3MSf Hf CHj WGdH GdHjgbjs
(3ChdgG (B:s
(3CMSfJ CMSfJ eG CHOYJ jG bjhe CeG HYO agPG eNJUQ ai Yde GdgjFI eTJed Ydi VhGHW cdjI hCeKdI LRFjI eJVef dCcKQ GdeSGFd GdeTghQI s
(3BNQgG (B:s
(3Ke ef VQH GdCejGd ai CQHYI CdGa jMUd CUGHgG Ke ef VQHgG ai SJI jMUd ebOGQ TYjQGJgG hbS Ydjg eG ShGg hHGddg GdJhajb s
(3HgG CTcGd hQShe gfOSjIs
(3HgG fXGe GdJYbjHIs
(3eQJH Ydi ebOeI ai KdGKI aUhd hKdGKI ebGUOs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs